They know not what they do - Valtonen, Jussi (Oneworld, 2017)
Joe Chayefski has got what he always wanted: a reputation as one of America's top neuroscientists, a beautiful wife and two perfect daughters. But his carefully created idyll is threatened when his Baltimore neuroscience lab is targeted by animal rights activists. The attack is followed by a phone call from Joe's ex-wife in Finland. Two decades have passed since he abandoned Alina and their young son, Samuel, returning to America to advance his career. Now Samuel is somewhere in the States, and Alina fears he is looking for revenge. As Joe struggles to protect his new family from the increasing threat of violence - and to save his eldest daughter from the clutches of an unscrupulous tech company - he is forced to reconsider his priorities and take drastic action to save those he loves.